RELATIONSHIP ANALYSIS OF THE PAYROLL SYSTEM WITH THE PERFORMANCE OF SALES EMPLOYEES IN PT.MULTI GARMEN JAYA - Esa Cahyaningati; Muchamad Arif (NAROTAMA UNIVERSITY, Indonesia, 2019)
The problem in this study is whether there is a significant relationship between the recitation system and employee performance at PT Multi Garmen Jaya. The purpose of this study was to determine the relationship between the recitation system and employee performance at PT Multi Garmen Jaya. This research was conducted on employees of the sales force of PT Multi Garmen Jaya. Which was done by formulating hypotheses to answer the problems formulated in the statement? The sample used was 60 respondents, the type of data needed (quantitative), the data collection method (primary). Data collection techniques are (observation and questionnaires). The sampling method uses the entire employee. The research instrument test used the validity test, reliability test, and cross-tab chi-square test. Testing the validity, reliability, and chi-square crosstab were carried out using the SPSS 16.0 program. by producing a level of bonus relationship (X1) with employee performance (Y) of, 000 with a significance level of <0.05. The relationship between overtime (X2) and employee performance (Y) is 000-, 001 with a significance level of <0.05, while the relationship between incentives (X3) and employee performance (Y) is 000 with a significance level of <0.05. Based on the hypothesis testing conducted, it can be seen that bonuses have a significant and significant relationship with employee performance. Overtime has a significant and significant relationship with employee performance, while incentive has a significant and significant relationship with employee performance.